Governance in the Muslim world: Exploring the Post-WWII era - Quddus, S. M. Abdul (2011)
This paper is based on empirical data about power relationships and governance in the 47 Muslim Majority Countries (MMCs). The paper argues that most MMCs are not unique in relation to governmental systems and have owed predominantly to the “syncratic” character of states where the governance system is based on clientelism (AKA the patron-client model of politics), commonly note the existence of loose coalition of both modern and traditional elites, who tend to foster economic and political changes without changing the complex privilege-obligation relationships among different unequal players or the status or “tradition” of the society. Our point of departure is that such a configuration of power relationships in MMCs have impinged on governance, conflicts and coercions, composition and imposition, as well as distribution of power in the MMCs. This paper draws the conclusion that the answer of the question of why democratic governance, autonomy and freedom of choice in administration, democracy, secularism, pluralism are not embedded in most MMCs, may be found in the explanation about influence of colonialism, the role and interests of individuals who occupy important political/administrative positions in the state-machineries, and the structural setting within which political acts are performed in the MMCs.